A Forgotten Tale of Lurking Engagement and Social Media-Based Brand Communities. Issue 2 (3rd April 2023) - Farhat, Kashif; Aslam, Wajeeha; Mokhtar, Sany Sanuri Mohd; de Luna, Iviane Ramos
Abstract: The study is motivated by the lack of comprehension on how lurking and posting engagement are driven by hedonic vs. utilitarian brands in social media-based brand communities (SMBBC). Survey responses of 229 social media customers comprising group 1 for hedonic brands ( n  = 126) and group 2 for utilitarian brands ( n  = 103) were included in a multigroup analysis (MGA). PLS-SEM modeling results indicate that economic and entertainment needs of customers are significantly related to lurking engagement for hedonic brands. In contrast, identification and information needs of customers are significantly related to posting engagement for utilitarian brands. Importantly, lurking engagement appears more significantly related to brand loyalty compared to posting engagement. The study extends several insights on lurking and posting engagement to design brand type-oriented social media marketing strategies. Findings of the study also enrich the Uses and Gratification Theory in the context of lurking and posting engagement.